PENGANGGURAN USIA MUDA DI JAWA BARAT (MENGGUNAKAN DATA SAKERNAS) - Wardhana, Adhitya; Kharisma, Bayu; Ibrahim, Yayuf Faridah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The high level of open unemployment at a young age in West Java Province is a crucial issue in the field of employment. This study aims to determine the factors that influence youth unemployment in West Java Province at the micro level. The results of the logistic regression analysis show that age, marital status, status in the household, education and household size have a significant impact on the probability of unemployment at a young age in West Java.